IMPACT OF MACROECONOMIC FACTORS ON THE BANKING SECTOR IN UZBEKISTAN - Mamedova Guzalkhan Kozimovna (Zeta Repository, 2023)
In the article, the impact of macroeconomic factors on the banking sector in Uzbekistan was studied, the experience of foreign countries was considered in this research, existing problems and several measures to improve the banking sector in Uzbekistan were developed, and conclusions were drawn.